The Accountability Concept in Public Administration Theory: Conceptual Development from the Past to the Present - Kreangpun, Teerapon (Journal of Social Sciences Naresuan University, 2022)
In the shade of the Governance concept, the accountability concept has been part of the current governance paradigm of Public Administration Theories. The accountability become a new concept that appear with governance. This research finds out that has the accountability concept just been defined as current public administration theory? And how does the development of accountability concept in the public administration theories era? The study is the qualitative research with documentary and textual analysis. The result of research found that the explanation of accountability relationship has appeared since the classical public administration theory era but doesn’t use the term “Accountability” directly. The form of accountability has developed Internal Accountability to External Accountability and has more complexity in each era of public administration theories.